Tuning the electronic conductivity of porous nitrogen-doped carbon nanofibers with graphene for high-performance potassium-ion storage. Issue 16 (21st July 2021) - Niu, Ping; Wang, Peisan; Xu, Yang; Li, Zhiqiang; Wei, Lingzhi; Yao, Ge; Wang, Junzhong; Zheng, Fangcai
Abstract : In the designed graphene/porous nitrogen-doped carbon nanofibers, graphene can improve the electronic conductivity of the composite materials, and a large amount of mesopores provided much more exposed N-doped active sites for adsorbing K + . Abstract : We report a hybrid structure of graphene/porous nitrogen-doped carbon nanofibers (G-PCNFs) with pronounced potassium-storage performances in terms of specific capacity, long-term cycling stability, and rate capability. In this structure, graphene (G) favors the transfer of electrons to enhance the conductivity, ensuring good rate capability for PIBs. Moreover, the porous structure has ample exposed N-doped active sites to adsorb K + to improve the capacitive contribution beyond the intercalation mechanism. As a result, the resulting G-PCNFs exhibit a highly reversible capacity of 358 mA h g −1 at 0.1 A g −1 after 200 cycles, outstanding rate performance (101 mA h g −1 at 5 A g −1 ) and ultralong cycling stability (276 mA h g −1 at 2 A g −1 after 2000 cycles). This work provides a new strategy for constructing carbonaceous anodes to achieve superior potassium-storage performances.